2016
DOI: 10.1002/jlcr.3359
|View full text |Cite
|
Sign up to set email alerts
|

Review: radiolabeled polymers containing covalently bound3Hand14C

Abstract: Radiolabeled compounds are invaluable tools used to study synthetic and biological processes. Radiolabeled polymers find uses in mechanistic pathway elucidation, bioincorporation studies, biodegradation studies, and drug delivery applications. This literature review examines the syntheses (or biosyntheses), physical properties, and applications of radiolabeled polymers which contain covalently bound tritium and carbon-14 atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…In vivo responses such as edema, bioresorption and deformation of the implant were observed through MRI [111]. Wolf extensively reviewed the radiolabeled polymers containing covalently bound 3 H and 14 C materials as benchmark tool for in vivo and in vitro studies for detection of polymer degradation, elucidation of mechanistic approach, bio-incorporation approach and drug delivery[115]. The extent of biodegradation was assessed by high-performance liquid chromatography (HPLC), mass spectrometry (MS) and 14 C radiolabel release.…”
mentioning
confidence: 99%
“…In vivo responses such as edema, bioresorption and deformation of the implant were observed through MRI [111]. Wolf extensively reviewed the radiolabeled polymers containing covalently bound 3 H and 14 C materials as benchmark tool for in vivo and in vitro studies for detection of polymer degradation, elucidation of mechanistic approach, bio-incorporation approach and drug delivery[115]. The extent of biodegradation was assessed by high-performance liquid chromatography (HPLC), mass spectrometry (MS) and 14 C radiolabel release.…”
mentioning
confidence: 99%
“…Radiolabeled materials have been shown to be a highly useful tool for other materials with significant analytical sensitivity challenges to enable studies at environmentally relevant concentrations, including polydimethylsiloxane (Kukkonen & Landrum, 1995;Tolle et al, 1995;Watts et al, 1995), polyacrylic acid (Larson et al, 1997), polyethylene glycol (Abdalla et al, 2005), and surfactant polymers, such as alcohol ethoxylates, alkyl ethoxy sulfates, and alkyl sulfates (Nuck & Federle, 1996;Steber & Wierich, 1985). Use of radiochemical labeling with 3H has been especially useful for quantifying exposure in several environmental polymer fate and effects studies as reported in the literature (Malik & Letey, 1991;Smith & Oehme, 1991;Wolf, 2016) and also in our laboratories (S. Belanger, Procter & Gamble FIGURE 3 Ratio of trophic sensitivities to cationic polymers. All ratios were constructed based on standard acute toxicity tests conducted using the same test material.…”
Section: Experimental Factors May Alter Observed Environmental Effectsmentioning
confidence: 99%
“…The detection of intact drug carriers inside the brain as well as carrier-drug dissociation monitoring through this type of techniques is still challenging and it is rarely shown. The use of radiolabelled polymers and/or drugs incorporating 14 C, and 3 H can contribute to this goal (Wolf, 2016).…”
Section: Additional Design Considerations and Strategiesmentioning
confidence: 99%